Ellie steps up to the plate - Barkley, Callie (Barkley, Callie. Critter Club, 2018)
When Ellie joins a softball team, she quickly realizes that the sport is harder than it looks! Is she meant only for the stage, not the field? And what happens when Ellie goes searching in the woods near the field for a stray ball and finds an injured baby deer?!